2021
DOI: 10.3390/polym13111681
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Cytotoxic Activity Enhancement of α-Mangostin in Chitosan-Kappa Carrageenan-Loaded Nanoparticle against MCF-7 Cell Line

Abstract: α-mangostin (αM), a xanthone derivative compound isolated from the extract of mangosteen pericarp (Garcinia mangostana L), has potential anticancer properties for breast cancer. However, it has poor solubility in water and low selectivity towards cancer cells. The polymeric nanoparticle formulation approach can be used to overcome these problems. In this study, a chitosan biopolymer-based αM polymeric nanoparticle formulation was encapsulated using kappa carrageenan (αM-Ch/Cr) as a novel carrier for breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 54 publications
1
20
1
Order By: Relevance
“…In another study, the cytotoxicity of water-soluble β -cyclodextrin-coated α -mangostin polymeric nanoparticles on A549 lung cancer cells was enhanced by 2.1-fold in comparison with free α -mangostin [ 39 ]. Wathoni and colleagues have demonstrated that α -mangostin chitosan-loaded kappa carrageenan nanoparticles (IC 50 of 4.7 µ g/mL) exhibited a higher antiproliferative activity on MCF-7 cells than drug solution (IC 50 of 8.2 µ g/mL) [ 40 ], in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, the cytotoxicity of water-soluble β -cyclodextrin-coated α -mangostin polymeric nanoparticles on A549 lung cancer cells was enhanced by 2.1-fold in comparison with free α -mangostin [ 39 ]. Wathoni and colleagues have demonstrated that α -mangostin chitosan-loaded kappa carrageenan nanoparticles (IC 50 of 4.7 µ g/mL) exhibited a higher antiproliferative activity on MCF-7 cells than drug solution (IC 50 of 8.2 µ g/mL) [ 40 ], in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Cytotoxicity in MCF-7 cells showed an increase in nanoparticle activity compared to free α-mangostin. The IC 50 of α-mangostin, α-mangostin-chitosan nanoparticle, and α-mangostin-chitosan-kappa carrageenan was 8.2, 6.7, and 4.7 g/mL, respectively [79].…”
Section: Chitosan-kappa Carrageenan Nanoparticlesmentioning
confidence: 92%
“…The physicochemical and biological characteristics of CSNPs are strongly influenced by their MW and surface charge [ 22 , 23 , 24 , 25 ]. The surface charge of the NPs impacts the accumulation of NPs at the target site, stability, cellular uptake, protein adsorption applications, and distribution throughout the body.…”
Section: Introductionmentioning
confidence: 99%
“…Modified CS can be made into multilayer composites by combining with polymers and other parts to change the properties of CS for certain biomedical applications, such as sodium alginate and chitosan [ 31 ]. CS can be encapsulated using kappa carrageenan [ 22 ] and Diethyl curcumin disuccinate [ 32 ]. CS–NPs were modified with either biotin or biotin and avidin [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation